Impact of Advertisement on Audience Purchase Intention: A Case Study of the Bhramyoman Theatre Industry of Assam - Panchamrita Sarma, Dr. Samannoy Baruah (Journal of Daoist Studies, 2026)
A distinctive habit which lead to formation of human civilisations is communal entertainment. Evidences of people gathering for celebrations and merrymaking even in ancient times is found in the cave and temple inscriptions. For these communal merrymaking, specific ritualistic art forms developed. Also, the importance of music, dance and drama for societies has emphasised through its trail being traced back to divine origin. Theatre was a key factor in the development of the two most notable human settlements in the west, the Greek and Roman civilizations. Greek plays are thought to have originated from celebrations of the birth of their god, Dionysus, son of Zeus. Greek tragedies originated from the catharsis, or intense emotion-driven dances, that were performed during the two festivals honouring the god Dionysus. Greek comedy and satire plays were later produced to give audiences a respite from tragic emotions, or to give drama a different emotional flavor. Since ancient times, drama has served as a main source of entertainment in India. The Vedas, which govern all aspects of Indian culture, have established the standard for drama in that country. The Natya Veda, written by Lord Brahma, is credited with evolving the idea of entertainment by incorporating ideas from the other four Vedas—the Rig, Sama, Yajur, and Atharva. After learning the craft, Sage Bharata and his sons began acting out plays for the gods. But performing art was brought to the mortals by King Nahusa (Varapande,1987). According to a different account of the origins of drama in ancient India, Sage Bharata wrote Natyasashtra, using music and words from the Rigveda. Over the years, the dramatical forms witnessed a lot of evolutions, adding financial gains to its agenda along with enjoyment, moral and religious preaching’s, The examination of performing arts as an economic activity has been highlighted by (Towser, 2010). The author describes the performing arts as a service sector, emphasizing how ephemeral they are. Profit making is difficult because it requires utilization of all necessary resources every time, regardless of the number of audiences. The price elasticity of demand for this category of luxury goods needs careful consideration. Business growth necessitates understanding ideas like rational addiction, learning by consumption, and habit formation (Seaman, 2006). Thus, we see performing arts are profitable endeavours, research on their economic aspects is imperative. As an illustration of the statement, consider the Assamese bhramyoman theatre sector, which since its founding in the 1960s has catered to the financial interests of various stakeholders. (In Ross, 2017)